Directory of research and development projects in agriculture, forestry and natural resources in the Philippines program year 1992 on-going and completed by commodity. - Philippine Council for Agriculture, Forestry and Natural Resources Research and Development (Los Banos, Laguna Management Information Services Division, PCARRD, 1992)
This directory is divided into two sections: crops sector and environment sector. Each section lists ongoing and completed development and research and development projects. The crops sector is divided into 12 areas: coconut and palm oil, corn and sorghum, fiber crops, fruit crops, legumes, ornamental horticulture and medicinal plants, plantation crops, rice and other cereal grains, root crops, sugarcane, tobacco, vegetables. The environment section is divided into the following areas: agricultural ecosystem, coastal zone and freshwater ecosystem, forest ecosystem, grassland and degraded ecosystem, urban ecosystem and upland farms ecosystem. Data is divided into 16 columns: item number, research code/research title/ researcher, duration, implementing agency, source of fund, and budgetary requirement. Other sectors that are part of this directory series but are not included in this volume are livestock, farm resources and systems, forestry, and socio-economics. The directory is available in both print and diskette forms.
Title from cover.
Keywords: Economic development projects -- Research -- Philippines -- Directories; Agricultural development projects -- Research -- Philippines -- Directories; Rural development projects -- Research -- Philippines -- Directories